STRATEGY FOR EMPOWERING MICRO BUSINESSES DURING THE COVID-19 PANDEMIC IN SURABAYA CITY - Yeni Yuli Wulandari; Lukman Arif (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
The impact of the Covid-19 pandemic was felt by the Micro Businesses assisted by the City of Surabaya. The Surabaya City Government is making efforts in an empowerment strategy so that the Micro Businesses fostered continue to produce in a pandemic. This study aims to analyze and describe the Empowerment Strategy of Micro-Business Assisted During the Covid-19 Pandemic in the City of Surabaya using the indicators of the empowerment strategy of Ismawan (1995) in Prijono & Pranaka (1996). This type of research is qualitative with data collection techniques in the form of observation, interviews, and documentation. The research location is in DP5A Surabaya City, DINKOPUM Surabaya City, DISDAG Surabaya City. The focus of research is on Strategies for Empowering Micro Businesses During the Covid-19 Pandemic in the City of Surabaya. Sources of research data are primary data and secondary data. The results of the study said that the empowerment of Micro Patronage during a pandemic covid-19 made by DP5A Surabaya, DINKOPUM Surabaya, DISDAG Surabayahas run according to the rules. However, empowerment still needs to be optimized and there is a need for better data collection for the Micro Businesses in each sub-district of the City of Surabaya.